Mesenchymal stromal cell apoptosis is required for their therapeutic function - Swee Heng Milon Pang (Nature Portfolio, 2021)
Mesenchymal stromal cells (MSCs) demonstrate therapeutic benefits in multiple diseases, but the mechanisms remain unclear as infused MSCs do not persist in the body. Here, the authors show that MSC apoptosis is an important mechanistic element, as MSCs rendered genetically incapable of apoptosis lose their ability to ameliorate disease.